HSP70 Ameliorates Septic Acute Kidney Injury via Binding with TRAF6 to Inhibit of Inflammation-Mediated Apoptosis - Zhang Y; Song C; Ni W; Pei Q; Wang C; Ying Y; Yao M (Dove Medical Press, 2022)
Yiqiu Zhang,1,* Chenlu Song,1,* Wei Ni,1,2 Qing Pei,1 Caixia Wang,1 Youguo Ying,3 Min Yao1 1Department of Plastic and Reconstructive Surgery, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Wuhan National Laboratory for Optoelectronics, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Intensive Care Unit, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Yao; Youguo Ying, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, 639 Zhizaoju Road, Shanghai, 200011, People’s Republic of China, Email my058@vip.sina.com; yingyouguo@sina.comPurpose: Acute kidney injury (AKI) is one of the most severe complications of sepsis, the pathological features of which are excessive inflammation and programmed cell death of resident renal cells. Heat shock protein 70 (HSP70) is a critical stress protein for repressing inflammation, however, its role in AKI is not fully understood. The current study aimed to determine the protective effect of HSP70 on septic AKI and its underlying mechanisms.Methods: Hsp70.1 knockout and wildtype mice were used for creating sepsis model by cecal ligation and puncture (CLP). Renal function, histological changes, pro-inflammatory cytokines, and apoptosis were analyzed with H&E, PAS, ELISA, western-blot, and immunofluorescence. Moreover, the effects of HSP70 on renal proximal tubular epithelial (HK-2) cells with LPS were assessed by measuring the levels of nuclear factor kappa B (NF-κB) signaling and downstream cytokines, viability, and apoptosis using western-blot, qRT-PCR, flow-cytometry, and immunofluorescence. Immunoprecipitate and immunoblotting were used for determining the interaction of HSP70 with tumor necrosis factor receptor-associated factor 6 (TRAF6). Exogenous HSP70 was applied to further identify its biological significance at the cellular and animal level.Results: Hsp70.1 deficiency significantly aggravated renal dysfunction with increasing serum levels of BUN, SCr, kidney injury molecule-1 (KIM-1), and neutrophil gelatinase-associated lipocalin (NGAL), and shortened survival in CLP mice. Furthermore, hsp70.1 knockout caused renal-tissue structural damage, especially proximal tubular, and inflammatory cascade and increased apoptotic cells, along with elevated Bax, caspase 3 and cleaved caspase 3, as well as decreased Bcl2 in vivo and vitro. Significantly, HSP70 directly interacted with TRAF6 in HK-2 cells, leading to suppression of inflammatory response and apoptosis. Moreover, exogenous HSP70 alleviated renal damage, decreased apoptosis and elevated survival rate in septic AKI in vivo and vitro.Conclusion: Our findings demonstrated that HSP70 played a critical role in sepsis-induced AKI via interaction with TRAF6 and inhibiting inflammation and apoptosis.Keywords: heat shock protein 70, sepsis, acute kidney injury, tumor necrosis factor receptor-associated factor 6, nuclear factor kappa B, apoptosis